Construct validity of attitude instrument of zakat payment behaviour amongst Muslim entrepreneur in Malaysia - Saad, Ram Al Jaffri; Mohd Nasir, Mohd Herry; Abdul Kadir, Dzarfan (2018)
Various studies state the importance of attitude in shaping one’s behaviour. But there is a gap in the assessment because the instruments have not been able to measure the competency of the factors as well as its conceptualization whether it is uni-dimensional or multidimensional factors. Therefore, it is necessary to prove the validity of the construct to the items in the instrument, especially in the context of zakat compliance behaviour. This study aimed to test that construct instrument validity. A mail survey was conducted among 227 Muslim businessmen in one of the states in Malaysia. Technic of data analysis to prove construct validity was factor analysis, and exploratory factor analysis. The results showed that from all items which were 24, there was 7 items stated as invalid and 17 items were valid. The analysis shows that the uni-dimensional data parameter can measure the construct and give significant effects. It is expected that the finding of this research can complete the constructive knowledge of the items of attitude and contribute to improving the measurement and conceptualization of this construct.